This feels like the right choice: how decision aids may facilitate affect-based valuation. Issue 6 (18th August 2022) - Jaffé, Mariela E.; Douneva, Maria; Reutner, Leonie; Greifeneder, Rainer
ABSTRACT: When individuals cannot make up their mind, they sometimes use a random decision-making aid such as a coin to make a decision. This aid may also elicit affective reactions: A person flipping a coin may (dis)like the outcome, and thus decide according to this feeling. We refer to this process as catalysing decisions and to the aid as catalyst . We investigate whether using a catalyst may not only elicit affect but also result in more affect-based decision making. We used different online studies that examine affect-driven decisions by investigating scope insensitivity (indirect behavioural measure) and self-reported weight given to feelings versus reasons in hypothetical donation decisions. Study 1a showed that a catalyst (a lottery wheel) lead to more scope insensitive (i.e. affect-driven) donations. Study 1b included several changes and did not replicate these results. Study 2 (preregistered) examined scope insensitivity but did not replicate previous results; Study 3 (preregistered) looked at the weight given to feelings versus reason. Although catalyst (compared to control) participants descriptively reported relying more on feelings, this difference did not reach significance. In contrast to lay beliefs, results do not indicate support for the hypothesis that using a catalyst results in more affect-based hypothetical donation decisions.